Outdoor Games Activities Model to Improve Students' Basic Movement and Creative Thinking Skills - Prasetiyo, Rahayu; Yunarta, Arsika; Andrianto, Joan Rhobi (STKIP PGRI Jombang, 2023)
The goal of this study was to see how the outdoor sports activities learning model affected students' basic mobility and creative thinking skills. The sample in this study included grade II students from SDN Kepanjen 2 Jombang, a total of 64 students, who were separated into two groups, 32 students as the experimental group and 32 students as the control group. The instrument used to measure students' basic motion is Test Gross Motor Development 2 (TGMD 2), and it was designed by researchers who have been tested for validity and reliability, with a validity value of 0.748 and a reliability value of 0.821. The data was analysed using an independent sample t test and SPSS 24. The findings of this study indicate that the outdoor sports activities model has an effect on pupils' basic movement abilities and creative thinking.